Non Catalytic Transesterification of Vegetables Oil to Biodiesel in Sub-and Supercritical Methanol: A Kinetic’s Study - Nyoman Puspa Asri; Siti Machmudah; W. Wahyudiono; S. Suprapto; Kusno Budikarjono; Achmad Roesyadi; Motonobu Goto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
Non catalytic transesterification in sub and supercritical methanol have been used to produce biodiesel from palm oil and soybean oil. A kinetic study was done under reaction condition with temperature and time control. The experiments were carried out in a batch type reactor at reaction temperatures from 210 °C (subcritical condition) to 290 °C (the supercritical state) in the interval ranges of temperature of 20 °C and at various molar ratios of oil to methanol. The rate constants of the reaction were determined by employing a simple method, with the overall chemical reaction followed the pseudo-first–order reaction. Based on the results, the rate constants of vegetables oil were significantly influenced by reaction temperature, which were gradually increased at subcritical temperature, but sharply increased in the supercritical state. However, the rate constants of soybean oil were slightly higher than that of palm oil. The activation energy for transesterification of soybean oil was 89.32 and 79.05 kJ/mole for palm oil. Meanwhile, the frequency factor values of both oils were 72462892 and 391210 min-1, respectively. The rate reaction for both of oil were expressed as -rTG = 72462892 exp(-89.32/RT)CTG for soybean oil and -rTG = 391210 exp(-79.05/RT)CTG for palm oil. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)